Revision in part of the genus Nebrioporus Régimbart, 1906, with emphasis on the N. laeviventris-group (Coleoptera: Dytiscidae) - Toledo, Mario (Zootaxa, 2009)
The genus Nebrioporus Régimbart, 1906 is reviewed and partially revised. The historical subgeneric divisions have not been subscribed to here because they fail to reflect the natural grouping within the genus. Instead, Nebrioporus has been divided into eight species-groups recognised and described with character analysis and keys for their identification. The N. laeviventris-group, comprising 4 subgroups and 13 species, has been revised. The N. depressus-group, the most speciose within the genus, is redefined and dealt with in detail with keys for the identification of the species and morphological illustrations accompanying the taxonomic discussion for selected species. The N. sansii-group, as here defined, is also keyed and illustrated and the species N. lynesi (J. Balfour-Browne, 1947) is revised and inserted into this group. Revisional notes are provided also for the following species: Nebrioporus canariensis (Bedel, 1881), N. capensis (Omer-Cooper, 1953), N. dubius (Aubé, 1838b), N. kiliani (Peyerimhoff, 1929), N. kilimandjarensis (Régimbart, 1906), N. seriatus (Sharp, 1882), N. simplicipes (Sharp, 1884), N. solivagus (Omer-Cooper, 1965), N. vagrans (Omer-Cooper, 1953). All revised species are provided with a short redescription, illustration of diagnostic characters and distributional analysis. For several species new distributional records are given. Illustrations of habitus and male characters are provided also for species not discussed in the text. A comprehensive checklist of the genus Nebrioporus is given, with synonyms. Two new species are described: N. amicorum sp.n. from Crete and N. sagartus sp.n. from Iran, both belonging to the N. laeviventris-group, the former described from material previously determined as Nebrioporus stearinus (Kolenati, 1854). Nebrioporus seriatus (Sharp, 1882) is found to be a member of the abyssinicus-group and inserted into previous identification keys. Nebrioporus suavis (Sharp, 1882) is here considered as a western subspecies of N. stearinus (new status as Nebrioporus stearinus suavis (Sharp)). New synonyms: Zimmermannius Guignot, 1941 = Nebrioporus Régimbart, 1906; Hydroporus walkeri Branden, 1885 = Hydroporus crotchi Preudhomme de Borre, 1871; Hydroporus variegatus Aubé, 1838a = Hydroporus stearinus Kolenati, 1845; Deronectes turca Seidlitz, 1887 = Hydroporus stearinus Kolenati, 1845; Potamonectes sulphuricola Zaitzev, 1951 = Hydroporus airumlus Kolenati, 1845. Lectotypes are designated for: Hydroporus clarkii Wollaston, 1862; Deronectes simplicipes Sharp, 1884; Deronectes anchoralis Sharp, 1884; Hydroporus kiliani Peyerimhoff, 1929; Deronectes seriatus Sharp, 1882; Deronectes arabicus Sharp, 1882; Deronectes islamiticus Sharp, 1882; Deronectes princeps Sharp, 1882; Hydroporus stearinus Kolenati, 1845; Deronectes suavis Sharp, 1882; Hydroporus crotchi Preudhomme de Borre, 1871; Hydroporus insignis Klug, 1833; Hydroporus semiclusus Walker, 1871; Deronectes hostilis Sharp, 1884; and Hydroporus melanogrammus Régimbart, 1899.